Formation of adriamycin--DNA adducts in vitro. - Cullinane, C (1994)
Adriamycin is known to induce the formation of adducts with DNA when reacted under in vitro transcription conditions. The factors affecting the extent of adduct formation were examined in order to establish the critical components and optimal conditions required for the reaction, and to gain insight into the nature of the DNA-adduct complex. There was a strong dependence on reaction temperature (with a 40-fold increase of adducts at 40-50 degrees C compared to 10 degrees C), pH (maximum adducts at pH 7), but little dependence on the oxygen level. There was an absolute requirement for a reducing agent, with adducts detected with DTT, beta-mercaptoethanol and glutathione, maximal adducts were formed at high levels of DTT (5-10 mM). Adducts were also formed with a xanthine oxidase/NADH reducing system, with increasing amounts of adducts detected with increasing NADH; no adducts were detected in the absence of either the enzyme or NADH. Of fourteen derivatives studied, only four yielded a similar extent of adduct formation as adriamycin; there was no absolute requirement for a carbonyl at C13 or hydroxyl at C14. Adducts were also observed with ssDNA but required a longer reaction time compared to dsDNA. The sequence specificity of adduct formation with ssDNA was examined using a primer-extension assay; almost all adducts were associated with a guanine residue. Overall, the results are consistent with a two-step reaction mechanism involving reductive activation of adriamycin, with the activated species then reacting with the guanine residues of either dsDNA or ssDNA.